Analysis Leverage to Anticipate The Risk of Financial The National Life Insurance Company - Nyoman Winata, I (Publisher Cv. Inara, 2023)
This study aims to (1) analyze the condition of the application of financial leverage and operational leverage of PT. Asuransi Jiwa XYZ; (2) analyze the impact of the condition of applying financial leverage and operational leverage on the company's financial risk. This research method uses a quantitative descriptive method with a case study approach at PT Asuransi Jiwa XYZ. The type of research data used is secondary data, namely quantitative data in the form of financial report data for 2018-2020 obtained from the company's website. Data analysis techniques are performed by calculating financial leverage ratios and operational leverage, then interpretation is carried out. Then an analysis of the impact of the condition of the company's leverage on its financial risk is carried out. The results achieved are that in general financial leverage and operational leverage indicate poor performance. Meanwhile, the impact of financial leverage and operational leverage on the company's financial risk also indicates poor performance, this is possibly due to the impact of the Covid-19 pandemic which has hit the country and even the whole world. However, data from the previous two years had shown indications of a significant decline in the company's financial performance.